2013
DOI: 10.1155/2013/782497
|View full text |Cite
|
Sign up to set email alerts
|

Astragalus Polysaccharide Suppresses Skeletal Muscle Myostatin Expression in Diabetes: Involvement of ROS-ERK and NF-κB Pathways

Abstract: Objective. The antidiabetes drug astragalus polysaccharide (APS) is capable of increasing insulin sensitivity in skeletal muscle and improving whole-body glucose homeostasis. Recent studies suggest that skeletal muscle secreted growth factor myostatin plays an important role in regulating insulin signaling and insulin resistance. We hypothesized that regulation of skeletal muscle myostatin expression may be involved in the improvement of insulin sensitivity by APS. Methods. APS was administered to 13-week-old … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 27 publications
3
29
0
Order By: Relevance
“…Astragalus polysaccharide (APS) is one of the active ingredients of Radix Astragali. It has been shown to exert various pharmacological activities, including antiinflammatory (Luo et al, 2015;Wei et al, 2016), antioxidant (Li et al, 2010;Yan et al, 2010), anti-diabetic (Liu et al, 2013), and anti-tumor activity (Yang et al, 2013). Furthermore, APS treatment ameliorated adjuvant-induced arthritis in rats in a dose-dependent manner (Jiang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Astragalus polysaccharide (APS) is one of the active ingredients of Radix Astragali. It has been shown to exert various pharmacological activities, including antiinflammatory (Luo et al, 2015;Wei et al, 2016), antioxidant (Li et al, 2010;Yan et al, 2010), anti-diabetic (Liu et al, 2013), and anti-tumor activity (Yang et al, 2013). Furthermore, APS treatment ameliorated adjuvant-induced arthritis in rats in a dose-dependent manner (Jiang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Astragalus species derivatives are crude drugs that have been widely used in traditional Chinese medicine for thousands of years as antiperspirant, antihypertensive, diuretic, and tonic treatments [8]. Studies from our group and others have indicated that Astragalus polysaccharide (APS), the extract from Astragalus membranaceus , exerts strong antitumor and antiglomerulonephritis activity [9] and effectively alleviates inflammation-induced artery endothelium cell injury and atherosclerosis [7].…”
Section: Introductionmentioning
confidence: 99%
“…Some insight about the effects of polysaccharides on the whole organism and muscle cells came from many studies that utilized Astragalus polysaccharides (APS) extracted from Astragalus membranaceus Bunge. For example, it was shown that APS lowered blood glucose in diabetic rats by increasing the overall phosphorylation of AMP‐activated protein kinase alpha subunit (AMPKα) and expression of glucose transporter 4 (GLUT‐4) gene in skeletal muscles (M. Liu et al, ; Zou, Mao, Wang, Liu, & Ou‐Yang, ). In C2C12 mouse myotubes, APS ameliorated palmitate induced insulin resistance through the inhibition of NF‐κB activation and inhibition of extracellular signal‐regulated kinase (ERK) (M. Liu et al, ; Zhao, Zhang, Ding, Wang, & Li, ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, it was shown that APS lowered blood glucose in diabetic rats by increasing the overall phosphorylation of AMP‐activated protein kinase alpha subunit (AMPKα) and expression of glucose transporter 4 (GLUT‐4) gene in skeletal muscles (M. Liu et al, ; Zou, Mao, Wang, Liu, & Ou‐Yang, ). In C2C12 mouse myotubes, APS ameliorated palmitate induced insulin resistance through the inhibition of NF‐κB activation and inhibition of extracellular signal‐regulated kinase (ERK) (M. Liu et al, ; Zhao, Zhang, Ding, Wang, & Li, ). Likewise, a previous study revealed that APS stimulated the L6 muscle cells in dose‐ and time‐dependent manner (J. Liu et al, ).…”
Section: Resultsmentioning
confidence: 99%